Comparison of posterior capsule opacification at 360-degree square edge hydrophilic and sharp edge hydrophobic acrylic intraocular lens in diabetic patients - Bai, Ling (Int J Ophthalmol, 2015)
AIM: To compare posterior capsule opacification (PCO) degree and visual functions after phacoemulsification in eyes implanted with 360-degree square edge hydrophilic acrylic intraocular lens (IOL) (570C C-flex, Rayner) and sharp edge hydrophobic acrylic IOL (Sensar AR40e, AMO) in diabetic patients. METHODS: Sixty diabetic patients underwent uneventful phacoemulsification and randomly implanted one of the two IOLs. The PCO value was measured by retroillumination photographs and Evaluation of Posterior Capsule Opacification (EPCO) 2000 image-analysis software at 1, 6, 12, and 24mo after surgery. Visual acuity, and contrast sensitivity in photopic and mesopic conditions were also examined at each follow up time point. The incidence of eye that required Nd:YAG laser posterior capsulotomy were also compared. RESULTS: There was not any statistically significant difference in PCO scores between Rayner C-flex 570C group and Sensar AR40e group at each follow up time point. Visual acuity, Nd:YAG capsulotomy incidence and contrast sensitivity also had no significant difference during the 24mo follow-up. CONCLUSION: For diabetic patients, Rayner 570C C-flex and Sensar AR40e IOLs are same effective for prevent PCO. The 360-degree square edge design maybe is a good alternative technique to improve PCO prevention.